THE INCREASING PHENOMENON OF SECOND-HAND CLOTHES PURCHASE: INSIGHTS FROM THE LITERATURE - Halimin Herjanto; Jean Scheller-Sampson; Elisabeth Erickson (Jurnal Manajemen dan Kewirausahaan, 2016)
The global trend of second-hand clothing (SHC) consumption is significantly increasing and unstoppable. This trend has made, and will continue to make, a huge impact in the clothing industry in virtually every part of the world. However, the number of studies on SHC are still limited and more importantly, the findings are mixed and inconclusive. This study investigates the trend in SHC research between 1990 and 2014. 131 published academic articles from different disciplines were collected and content analyzed and the results indicate that SHC research was highly focused on the topics of consumption behavior, textile disposal behavior, and SHC trading related issues. In addition, the results also show that SHC research was mainly conducted from the consumers’ point of view. With the increasing interest in SHC, this study attempts to develop a better understanding of SHC phenomena and provide clear future research directions to scholars in designing SHC related research.